Managing the Provision of Non-Formal Secondary Education in Tanzania: The Emerging Sustainability Issues - Shirima, Gennes Hendry (Papers in Education and Development, 2021)
This study examined the management of non-formal secondary education (NFSE)3 amidst high demand among out-of-school youths to determine its sustainability. Using NFSE as a case, this qualitative study subjected interview and documentary review data to content analysis. The study found no single, well-integrated and accountable organisational structure to engage harmoniously all the institutions responsible for managing NFSE practices. Parallel reporting systems, fragmented institutional linkages and unsystematic coordination of activities were rampart and caused inconsistencies and conflicting roles. Consequently, an uncontrolled number of shadow NFSE providers in the black market mushroomed and threatened its sustainability. Conclusively, NFSE was insufficiently integrated in the education institutional framework hence, lacked critical administrative support. Thus, NFSE practices need to be streamlined under a full-fledged and functional ANFE department for proper coordination and sustainable NFSE provision. Keywords: coordination, institutional framework, institutional linkage, organisational structure,